2013
DOI: 10.1021/nn4001269
|View full text |Cite
|
Sign up to set email alerts
|

Water-Based Thixotropic Polymer Gel Electrolyte for Dye-Sensitized Solar Cells

Abstract: For the practical application of dye-sensitized solar cells (DSSCs), it is important to replace the conventional organic solvents based electrolyte with environmentally friendly and stable ones, due to the toxicity and leakage problems. Here we report a noble water-based thixotropic polymer gel electrolyte containing xanthan gum, which satisfies both the environmentally friendliness and stability against leakage and water intrusion. For application in DSSCs, it was possible to infiltrate the prepared electroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 32 publications
1
50
0
Order By: Relevance
“…316,317 To this purpose, Ko and coworkers used xanthan gum (M n = 2 Â 10 6 ), a water soluble and environmentally friendly polysaccharide rich in hydroxyl groups ready to form a 3D network, the viscosity of which reversibly decreases upon application of an external stress. 318 After a thorough optimization of the stability of all the ingredients in the reactive formulation -a key aspect in this field, where apolar, polar and ionic substances are concurrently used -a 1 : 1 mixture of xanthan gum (3 wt% in H 2 O) and liquid electrolyte (PMII 4.0 M, I 2 0.30 M, TBP 1.5 M and GuSCN 0.20 M in MPN) was selected. As reported in Table 19, resulting aqueous DSSCs, both liquid and quasi-solid, showed higher V oc and FF, but lower J sc values with respect to the MPNbased liquid counterpart.…”
Section: Gel-polymer Aqueous Electrolytesmentioning
confidence: 99%
“…316,317 To this purpose, Ko and coworkers used xanthan gum (M n = 2 Â 10 6 ), a water soluble and environmentally friendly polysaccharide rich in hydroxyl groups ready to form a 3D network, the viscosity of which reversibly decreases upon application of an external stress. 318 After a thorough optimization of the stability of all the ingredients in the reactive formulation -a key aspect in this field, where apolar, polar and ionic substances are concurrently used -a 1 : 1 mixture of xanthan gum (3 wt% in H 2 O) and liquid electrolyte (PMII 4.0 M, I 2 0.30 M, TBP 1.5 M and GuSCN 0.20 M in MPN) was selected. As reported in Table 19, resulting aqueous DSSCs, both liquid and quasi-solid, showed higher V oc and FF, but lower J sc values with respect to the MPNbased liquid counterpart.…”
Section: Gel-polymer Aqueous Electrolytesmentioning
confidence: 99%
“…We previously reported that aqueous DSCs stored in the dark fort hree months maintained 90 %i nitial efficiency. [25] Nevertheless, the devices maintain over 80 %o ft heir originale fficiency after illumination for 90 h, whereas the value for liquid counterparts was 57 %a fter the same period,s uggesting that the stability for the gel type DSCs is improved. One of the well documented reasons for the improveds tability is ar eduction in the evaporation of solvents present in the electrolytes.…”
Section: Resultsmentioning
confidence: 97%
“…O'Regan and co-workersr ecently examined the stabilityofDSCs assembled with an acetonitrile electrolyte containing the [Co(bpy) 3 ] 2 + /3 + redox couple over ap eriod of 2000h of light soaking at 20 8Ca nd 1sun light intensity. [25,44] Witht his in mind,w ec arried out experiments to comparethe stability of the devices assembled with the aqueous gel electrolyte with that of devices made with corresponding aqueous electrolyte under white LED light illumination correspondingt o1sun (Figure 9a). We previously reported that aqueous DSCs stored in the dark fort hree months maintained 90 %i nitial efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gum XanthanþPVP, Gum tragacanth þ PVP and Gum Acacia þ PVP, Gum Acacia þ PVP presents better compatibility as it has stronger intermolecular interaction. In the same manner, among Gum Xanthan þ PEG, Gum Acacia þ PEG and Gum tragacanth þ PEG systems, Gum Tragacanth þ PEG has better compatibility [171].…”
Section: Xanthan Gummentioning
confidence: 89%